2017
DOI: 10.1155/2017/6765856
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of Bioelectrical Impedance Analysis and Other Methods in the Assessment of Nutritional Status in Patients with Liver Cirrhosis

Abstract: It is assumed that approximately 24–66% of patients with liver cirrhosis develop malnutrition. Numerous pathological processes lead to serious disorders of nutritional status in this group of patients. Malnutrition in the course of liver cirrhosis is associated with increased morbidity, complications, and low quality of life. Under these conditions, detection of malnutrition is of crucial importance. This review explores the complex mechanisms that lead to malnutrition in the course of liver cirrhosis and focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 98 publications
(84 reference statements)
0
26
0
Order By: Relevance
“…PhA score correlates with functional status. PhA is an important predictor of mortality [ 6 , 7 , 8 ], malnutrition in cancer [ 8 , 9 , 10 , 11 ], liver cirrhosis [ 12 ], diabetes [ 13 , 14 ], psoriasis [ 15 ], in chronic kidney disease treated with hemodialysis [ 16 ] and in heart failure [ 17 ]. Hence, PhA can be regarded as a reliable prognostic marker and should be considered as a screening tool for the identification of patients at risk of impaired nutritional and functional status [ 2 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…PhA score correlates with functional status. PhA is an important predictor of mortality [ 6 , 7 , 8 ], malnutrition in cancer [ 8 , 9 , 10 , 11 ], liver cirrhosis [ 12 ], diabetes [ 13 , 14 ], psoriasis [ 15 ], in chronic kidney disease treated with hemodialysis [ 16 ] and in heart failure [ 17 ]. Hence, PhA can be regarded as a reliable prognostic marker and should be considered as a screening tool for the identification of patients at risk of impaired nutritional and functional status [ 2 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…While many papers have promoted the use of BCA to detect malnutrition, 10,15,17,27,30,31 and speci c studies described the application of these techniques in clinical areas (e.g. elderly; 32 liver failure; [44][45][46] oncology; 47,48 renal disease; 49 and respiratory disease 26 ) none have applied this across a hospital dietetics department.…”
Section: Discussionmentioning
confidence: 99%
“…The SGA is commonly used to assess nutrition in cirrhotic patients. However previous studies reported its low sensitivity, in the majority of patients with liver cirrhosis [6,7].…”
Section: Introductionmentioning
confidence: 99%